2014
DOI: 10.1007/s12664-014-0459-x
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation for management of Clostridium difficile infection

Abstract: The widespread use of antibiotics has led Clostridium difficile infection (CDI) to become a common problem with pronounced medical and economic effects. The recurrence of CDI after treatment with standard antibiotics is becoming more common with the emergence of more resistant strains of C. difficile. As CDI is an antibiotic-associated disease, further treatment with antibiotic is best avoided. As the gut flora is severely disturbed in CDI, approaches that restore the gut microbiota may become good alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Manipulation of gut microbiota using probiotic, antibiotics, and fecal transplantation may be useful in IBS and IBD patients, further proving the role of dysbiosis and inflammation in the pathogenesis of a subset of patients. [52][53][54] In conclusion, up-regulation of TLR-4 and TLR-5 suggest that the innate immune system may play an important role in the pathophysiology of IBS. The up-regulation of pro-inflammatory cytokines (IL-6, CXCL-11, and CXCR-3) and down-regulation of the anti-inflammatory cytokine (IL-10) in patients with IBS-D than controls suggest the presence of low-grade intestinal inflammation in a subgroup of IBS patients.…”
Section: Discussionmentioning
confidence: 83%
“…Manipulation of gut microbiota using probiotic, antibiotics, and fecal transplantation may be useful in IBS and IBD patients, further proving the role of dysbiosis and inflammation in the pathogenesis of a subset of patients. [52][53][54] In conclusion, up-regulation of TLR-4 and TLR-5 suggest that the innate immune system may play an important role in the pathophysiology of IBS. The up-regulation of pro-inflammatory cytokines (IL-6, CXCL-11, and CXCR-3) and down-regulation of the anti-inflammatory cytokine (IL-10) in patients with IBS-D than controls suggest the presence of low-grade intestinal inflammation in a subgroup of IBS patients.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have shown that the bacteria content in sigmoid colon and anal canal can be up to 1,011 g wet weight, accounting for 20% of the stool weight. In healthy people, the Bacteroides and Bifidobacterium in intestinal tract account for about 50% of the total bacteria, but Escherichia coli and Enterococci are no more than 1% ( 14 ). Bifidobacterium and Lactobacillus are the intestinal symbiotic dominant bacterial communities, which form the bacterial flora, acidify the intestinal tract, inhibit the spoilage and pathogens, constitute the intestinal barrier, reduce toxins into the blood, produce the organic acids, stimulate the peristalsis, prevent constipation, synthesize the vitamins and amino acids, stimulate the body's immune system, decompose carcinogenic substances and reduce the occurrence of colon cancer ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…FMT may be administered to the proximal colon via colonoscope, the distal lower gastrointestinal tract via enema, rectal catheter, and the upper GI tract through a nasogastric tube, a nasoduodenal tube or a gastroscope. 14 We are hereby reporting our findings in a child with ulcerative colitis who was treated with fecal microbial transplantation at our institute. To the best of our knowledge, the use of FMT for the treatment of ulcerative colitis is being reported for the first time in India.…”
Section: Introductionmentioning
confidence: 90%